UPAYA PENINGKATKAN HASIL BELAJAR MAHASISWA PRODI PENDIDIKAN MATEMATIKA PADA MATA KULIAH ALJABAR LINIER DENGAN PEMBELAJARAN DARING MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM SOLVING - I Komang Sukendra; I Wayan Muliana; I Dewa Putu Juwana; I Made Surat (Widyadari : Jurnal Pendidikan, 2022)
Problem solving learning model is a learning model that presents material by confronting students with problems that must be solved. The aims of this study are (1) to determine whether there is a response and whether the application of the problem solving learning model with the zoom application can improve learning outcomes in answering questions in linear algebra courses. This type of research is classroom action research. The subjects of this research are 6th semester students of the Mathematics Education Study Program, Universitas PGRI Mahadewa Indonesia for the academic year 2021/2022, and the object of this research is a study of understanding linear algebra courses and student responses to problem solving learning models. In this study through four stages of the activity process which includes (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. Data collection techniques using test and observation methods. The results showed that (1) the application of the problem solving learning model could improve the ability to answer questions in linear algebra courses. (2) There is a positive response from students towards the application of problem solving learning models to improve the ability to answer questions in linear algebra courses for 6th semester students of the Mathematics Education Study Program, Universitas PGRI Mahadewa Indonesia for the 2021/2022 academic year.